Job preferences as revealed by employee initiated job changes - Christian Grund (Institute for the Study of Labor (IZA), 2011)
Many previous studies try to discover job preferences by directly asking individuals. Since it is not sure, whether answers to these surveys are relevant for actual behaviour, this empirical examination offers a new approach based on representative German data. Employees who quit their job and find a new one, compare the two jobs with respect to eight job characteristics: type of work, pay, chances of promotion, work load, commuting time, work hour regulations, fringe benefits and security against loss of job. It is argued that the observation of many improvements (and few declines) for a certain attribute indicates a particular relevance and high preference for this attribute. It turns out that pay and type of work are most important for employees in this sense. Differences across subgroups of employees with respect to individual characteristics such as sex and age are explored. Those between East- and West-Germany diminish over time.
urn:nbn:de:101:1-201112136758
Keywords: M5; J28; J63; 330; job characteristics; job changes; job preferences; quits; Arbeitsmobilität; Offenbarte Präferenzen; Arbeitsverhältnis; Lohn; Schätzung; Deutschland